A review of Sri Lankan Brignolia including the description of four new species (Araneae: Oonopidae) - Ranasinghe, U. G. S. L.; Benjamin, Suresh P. (Zootaxa, 2016)
Sri Lankan species of the genus Brignolia Dumitrescu & Georgescu, 1983 are reviewed and four new species are described: B. carlmulleri sp. nov., B. meemure sp. nov., B. ondaatjei sp. nov. and B. shyami sp. nov. All new species are described based on both sexes. New data on B. ambigua (Simon, 1893), B. parumpunctata (Simon, 1893), B. ratnapura Platnick et al., 2011 and B. trichinalis (Benoit, 1979) are given. A total of 10 species are now known from Sri Lanka. B. ambigua, B. carlmulleri sp. nov., B. meemure sp. nov., B. ondaatjei sp. nov., B. ratnapura, B. shyami sp. nov. and B. sinharaja are endemic to the island. A key and a distribution map for Sri Lankan Brignolia are provided.